Crafting Inconspicuous Luxury Brands Through Brand Authenticity in China - Wu, Zhiyan (Frontiers in Psychology, 2022)
Currently, we are witnessing a trend towards subtle or absent hints of luxury, reflecting the rise of inconspicuousness. We seek to address why and how Chinese luxury brand managers, instead of matching conspicuous branding of many Western brands, develop inconspicuous strategies and craft authentic attributes in their brand communication. In the Chinese luxury brand context, we use the ethnographic research method with in-depth interviews, perform field visits and analyze photographs of eight Chinese luxury brands with inconspicuous preferences to reveal three main themes contributing to inconspicuousness. First, an inconspicuous approach of Chinese luxury brands is derived from the rise of inconspicuous consumption in China and a rejection of status brands due to being less famous than well-known Western brands, superficiality of status branding, and limited production capability. Second, we argue that inconspicuous branding can encompass developing luxury brands that do not enable consumers to overtly display wealth and social status. Third, we identify three ways of crafting brand authenticity to build inconspicuous brands by using a) nature (places and rare raw materials); b) traditional and historical elements (the traditional Chinese craftsmanship and a sincere story) so that a sincere story of how meanings emerge from traditional symbols and how innovations are used in traditional heritage products is shown to represent the authentic value of Chinese inconspicuous luxury brands; and c) sustainability (raw materials, traditional craftmanship, luxury production process, and saving resources) to craft brand authenticity inconspicuously for Chinese luxury brands.